Error analysis: the correlation between justification inclusion and learners’ performance in an English grammar assessment / Nur Hidayah Md Yazid ... [et al.] - Md Yazid, Nur Hidayah; Malik, Melissa; Jelani, Sakinatul Ain; Md Naim, Irwan Affendi (Universiti Teknologi MARA Cawangan Kedah, 2023)
Error Analysis (EA) is regarded as an essential element in the English language which facilitates learners to identify and correct language errors that they have produced themselves or from other forms of discourse. Nevertheless, especially among learners of an English as a Second Language (ESL) program, their actual understanding of the reason for the errors might become undetermined if they do not provide the justification of the errors identified. Hence, there is a need to identify how ESL learners truly know the reasons behind every error made. This study investigated the relationship between error justification inclusion in an EA assessment for an English grammar course and post-secondary ESL learners’ performance at one higher learning institution in the Klang Valley. The study sought to examine if there was a significant relationship between justifications of EA and students’ performance. The quantitative method was utilized to analyse data using 131 samples from an error analysis assessment. Findings suggested that the inclusion of EA justification has a strong correlation with the students’ performance in the assessment.